Diversité génétique de l’allèle O dans des populations berbères - Silvayn Amory; Jean-Michel Dugoujon; Stéphanie Despiau; Francis Roubinet; Farha El-Chennawi; Antoine Blancher (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
We analysed the O allele polymorphism in a sample of 33 Berbers from the Siwa population, all of them of phenotype O and unrelated to one another. The results show an important genetic diversity considering the limited number of individuals under study. The population must have been in contact with other people in spite of the geographical and cultural isolation. Siwa was an important stopping place for caravans in the desert: it was subjected to many raids and armed conflicts. The frequencies of the O01 and O02 alleles are similar to those in the Amizmiz Berbers in Morocco. Three new alleles were discovered in the Siwa population. These results confirm the importance of studying the molecular polymorphism of the O allele to better understand the genetic history of populations.